Peran Belanja Infrastruktur Jalan, Kesehatan, dan Pendidikan Terhadap PAD di Kalimantan Timur - Ramadhani, Muhammad Harits Zidni Khatib; Rinaldi, Muhammad; Fitria, Yunita (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the impact of road infrastructure, health, and education expenditures on Local Own-Source Revenue (PAD) in regencies and cities in East Kalimantan Province. By evaluating these expenditures, this study seeks to determine their effectiveness in increasing local fiscal capacity and supporting sustainable economic growth.. Methodology/Approach: This study employs quantitative methods using panel data regression analysis with data collected from 2018 to 2023. This study applies E-Views software to conduct a regression analysis while performing classical assumption tests and model selection to determine the most appropriate regression model. Results/Findings: The findings indicate that Road infrastructure and education expenditures do not have a significant impact on PAD, whereas health expenditures show a marginal positive effect. The R-squared value of 0.4806 suggests that these variables explain 48% of the PAD variation, while the adjusted R-squared of 0.4206 indicates moderate explanatory power. Conclusion: The study concludes that while infrastructure spending is essential, health sector investments play a more immediate role in increasing PAD by improving workforce productivity. These findings suggest that local governments should prioritize strategic spending allocation in sectors with higher direct fiscal returns. Limitations: This study is limited to five years of data (2018-2023) and focuses solely on three expenditure categories without incorporating other factors such as industrial activity, tourism, and demographic shifts, which may also influence PAD. Contribution: This study provides empirical insights for local governments and policymakers on the effectiveness of infrastructure spending in enhancing local revenue.